CCNP ONT portable command guide - Empson, Scott (Cisco self-study., 2008)
All the ONT 642-845 commands in one compact, portable resource Preparing for the CCNP® certification? Working as a network professional? Here are all the CCNP-level commands for the ONT exam you need in one condensed, portable resource. The CCNP ONT Portable Command Guide is filled with valuable, easy-to-access information and is portable enough for use whether you're in the server room or the equipment closet. This book will help you memorize commands and concepts as you work to pass the CCNP ONT exam (642-845). The guide summarizes all CCNP certification-level Cisco IOS® Software commands, keywords, command arguments, and associated prompts, providing you with tips and examples of how to apply the commands to real-world scenarios. Sample configurations throughout the book provide you with a better understanding of how these commands are used in simple network designs. The topics in this portable command guide cover how to do the following: Describe Cisco VoIP implementations Describe QoS considerations Describe DiffServ QoS implementations Implement AutoQoS Implement WLAN security and management Scott Empson is currently the assistant program chair of the bachelor of applied information systems technology degree program at the Northern Alberta Institute of Technology in Edmonton, Alberta, Canada, teaching Cisco® routing, switching, and network design courses in certificate, diploma, and applied degree programs at the post-secondary level. Hans Roth is an instructor in the electrical/electronic engineering technology department at Red River College in Winnipeg, Canada. Access all CCNP ONT commands-use as a quick, offline resource for research and solutions Logical "how-to" topic groupings provide one-stop research Great for review before taking the CCNP ONT certification exam Compact size makes it easy to carry with you, wherever you go "Create Your Own Journal" section with blank, lined pages allows you to personalize the book for your needs This book is part of the Cisco Press® Certification Self-Study Product Family, which offers readers a self-paced study routine for Cisco certification exams. Titles in the Cisco Press Certification Self-Study Product Family are part of a recommended learning program from Cisco that includes simulation and hands-on training from authorized Cisco Learning Partners and self-study products from Cisco Press. Category: Cisco Press-Cisco Certification Covers: CCNP ONT Certification 642-845 $24.99 USA / $26.99 CAN